2020
DOI: 10.1021/acs.analchem.0c04688
|View full text |Cite
|
Sign up to set email alerts
|

Tributylhexadecylphosphonium Modification Strategy to Construct Gold Nanoprobes for the Detection of Aqueous Cr(III)–Organic Complexes

Abstract: Most metal probes based on gold nanoparticles (AuNPs) are designed for free metal ions in synthetic waters, and very few are applicable in the detection of metal–organic complexes ubiquitous in real water samples. In this study, we proposed a novel colorimetric nanoprobe strategy for complexed Cr­(III) species based on the analyte-induced aggregation of AuNPs, as coated by a cationic surfactant tributylhexadecylphosphonium bromide (THPB) instead of traditional carboxyl modifiers. Such a detection system could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…All electrolytic materials are processed to a uniform size (50 × 10 × 2 mm for electrolysis and 10 × 10 × 2 mm for electrochemical tests) and cleaned in ethanol and DIW for 8 and 10 min respectively with ultrasonic assistance. Au and Ag particles were selected as modifiers considering their catalytic properties. , The preparation process of the modified electrode is shown in Figure S2 (Supporting Information), and briefly, the foam electrode is first etched in 6 mol L –1 HCl to remove the possible oxide layer. Then, a three-electrode system composed of a nickel foam electrode (NFE) (working electrode), Ag/AgCl (reference electrode), and Pt wire (auxiliary electrode) is used to precipitate gold or silver by cyclic voltammetry within the window voltage range of 0.2 to −0.6 V for 30 min at a scan rate of 10 mV s –1 .…”
Section: Methodsmentioning
confidence: 99%
“…All electrolytic materials are processed to a uniform size (50 × 10 × 2 mm for electrolysis and 10 × 10 × 2 mm for electrochemical tests) and cleaned in ethanol and DIW for 8 and 10 min respectively with ultrasonic assistance. Au and Ag particles were selected as modifiers considering their catalytic properties. , The preparation process of the modified electrode is shown in Figure S2 (Supporting Information), and briefly, the foam electrode is first etched in 6 mol L –1 HCl to remove the possible oxide layer. Then, a three-electrode system composed of a nickel foam electrode (NFE) (working electrode), Ag/AgCl (reference electrode), and Pt wire (auxiliary electrode) is used to precipitate gold or silver by cyclic voltammetry within the window voltage range of 0.2 to −0.6 V for 30 min at a scan rate of 10 mV s –1 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the shifts of both N 1s peak and Cr 2p peak, we postulate that the citrate moiety of the Cr(III)−citrate complexes interacts with the positive head group of CTAB through strong electrostatic interactions, weakening the coordination interaction between Cr(III) and citrate. 10,35 To further elucidate the interaction between Cr(III)−citrate and CTAB, Cryo-TEM characterization was carried out to visualize the formation of the Cr(III)−citrate/CTAB complex during coagulation. In either Cr(III)−citrate (Figure 5A) or CTAB solution (Figure 5B), no aggregation sign could be distinguished.…”
Section: Methodsmentioning
confidence: 99%
“…31−34 Very recently, we developed a new gold nanoprobe by using cationic surfactants as the modifier for selective and ultrasensitive analysis of various Cr(III)−organic complexes in contaminated waters. 35 The unique interaction between the target metal complexes and the cationic surfactant, that is, tributylhexadecylphosphonium bromide (THPB), was revealed to be responsible for such specific recognition in complex matrixes. As inspired by these interesting studies, here, we reported a proof-of-concept coagulation strategy for the elimination of heavy metal complexes via the formation of ternary selfassemblies using cationic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…How to cite this article: Y. Li, X. Tian, J. Zhang, L. Qiu, X. Wang, S. Wu, Y. Zhang, M. Zhu, E. Gao, Appl Organomet Chem 2021, 35 (12), e6414. https:// doi.org/10.1002/aoc.6414…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…[10,11] After the organism is taken, about 30%-90% of the intake is excreted from the organism in the form of mother or metabolites. [12] Long-term exposure to the environment usually causes pollution of surface water, groundwater, and drinking water. [13][14][15][16][17][18][19][20][21] The frequent use of antibiotics leads to their continuous input in the environment.…”
Section: Introductionmentioning
confidence: 99%